Evaluation of Serum AMH, INHB Combined with Basic FSH on Ovarian Reserve Function after Laparoscopic Ovarian Endometriosis Cystectomy - Tang, Yan; Li, Yanning (Frontiers in Surgery, 2022)
Objective To detect the levels of serum anti-mullerian hormone (AMH), inhibin B (INHB) and basal follicle stimulating hormone (bFSH) after laparoscopic ovarian endometriotic cyst removal, and to analyze the serum AMH, INHB, bFSH evaluation of the level of postoperative ovarian reserve function. Methods From June 2019 to December 2021, 124 patients underwent laparoscopic ovarian endometriosis cystectomy in our hospital were selected, and the serum AMH, INHB, bFSH level, sinus follicle count (AFC) number of all patients before and after operation were detected and compared. According to the results of postoperative testing, all the patients were divided into normal group (n=86), hypothyroid reserve function (DOR) group (n=27), and premature ovarian failure (POF) group (n=11). Pearson correlation was used to analyze the correlation between serum AMH, INHB, bFSH levels and postoperative ovarian reserve function. The receiver operating characteristic curve (ROC) was drawn。 Results After operation, the levels of serum AMH, INHB and AFC in the DOR group and POF group decreased compared with those before the operation, and the serum bFSH levels increase (P<0.05). After operation, the levels of serum AMH, INHB and AFC in DOR group and POF group were lower than those in normal group, the level of serum bFSH was higher, and the levels of serum AMH, INHB and AFC in POF group were lower than those in DOR group, the level of serum bFSH was higher (P<0.05). Pearson analysis showed that serum AMH and INHB levels were negatively correlated with bFSH (r=-0.615, P=0.011, r=-0.742, P=0.002), and positively correlated with the number of AFC (r=0.659, P=0.007, r=0.718, 0.003), the serum bFSH level was negatively correlated with the number of AFC (r=-0.597, P=0.018). Conclusion Serum AMH and INHB levels decrease and bFSH levels increase after laparoscopic ovarian endometriotic cyst removal, which are closely related to the postoperative ovarian reserve function. These three indicators all can be used as reference index for evaluating ovarian reserve function after ovarian cystectomy. Combined indicators to evaluate ovarian reserve function after ovarian cystectomy will improve the detection rate significantly.